The effect of lightning impulse characteristics and line arrester to the lightning protection performance on 150 kV overhead lines: ATP-EMTP computational approach - Fri Murdiya; Febrizal Febrizal; Cecilia Stevany; Havel Alindo Sano; Firdaus Firdaus (National Research and Innovation Agency, 2019)
This simulation study presents the effect of lightning strikes on the performance of arresters at 150 kV overhead lines. Lightning strikes have several parameters that affect the performance of line arresters (LA), namely lightning charge, and impulse energy. The simulation was attempted by injection of a direct strike to the ground wire with the peak voltage of 10 MV. The peak voltage was varied in terms of wavefront time (Tf) and the duration of lightning impulses (tau). In order to calculate current, charge and impulse energy of LA from various variations of Tf and tau, the trapezoidal numerical integration method is used. The current and impulse energy arising due to direct strikes and various variations of Tf and tau will be compared for each phase so that the influence of Tf and tau can be obtained from the performance of the LA and the current charge and impulse energy values are still within the limits of the IEEE C62.11 standard. The installation of LA and the position of arresters affected the peak voltage of lightning on the phase line when lightning struck it. The line arresters provide a drop in the peak voltage of lightning in phase lines. By installing line arresters in each tower, it will reduce the peak voltage of lightning on the phase line more significantly than the standalone line arrester. It is shown that the line arresters have to install at least six towers to reduce the peak voltage in the phase lines.